What is the pipeline for future medications for obesity? - Melson, Eka; Ashraf, Uzma; Papamargaritis, Dimitris; Davies, Melanie J (International journal of obesity (2005), 2025)
Obesity is a chronic disease associated with increased risk of obesity-related complications and mortality. Our better understanding of the weight regulation mechanisms and the role of gut-brain axis on appetite has led to the development of safe and effective entero-pancreatic hormone-based treatments for obesity such as glucagon-like peptide-1 (GLP-1) receptor agonists (RA). Semaglutide 2.4 mg once weekly, a subcutaneously administered GLP-1 RA approved for obesity treatment in 2021, results in 15-17% mean weight loss (WL) with evidence of cardioprotection. Oral GLP-1 RA are also under development and early data shows similar WL efficacy to semaglutide 2.4 mg. Looking to the next generation of obesity treatments, combinations of GLP-1 with other entero-pancreatic hormones with complementary actions and/or synergistic potential (such as glucose-dependent insulinotropic polypeptide (GIP), glucagon, and amylin) are under investigation to enhance the WL and cardiometabolic benefits of GLP-1 RA. Tirzepatide, a dual GLP-1/GIP receptor agonist has been approved for glycaemic control in type 2 diabetes as well as for obesity management leading in up to 22.5% WL in phase 3 obesity trials. Other combinations of entero-pancreatic hormones including cagrisema (GLP-1/amylin RA) and the triple agonist retatrutide (GLP-1/GIP/glucagon RA) have also progressed to phase 3 trials as obesity treatments and early data suggests that may lead to even greater WL than tirzepatide. Additionally, agents with different mechanisms of action to entero-pancreatic hormones (e.g. bimagrumab) may improve the body composition during WL and are in early phase clinical trials. We are in a new era for obesity pharmacotherapy where combinations of entero-pancreatic hormones approach the WL achieved with bariatric surgery. In this review, we present the efficacy and safety data for the pipeline of obesity pharmacotherapies with a focus on entero-pancreatic hormone-based treatments and we consider the clinical implications and challenges that the new era in obesity management may bring.